ANNONCES DE PRESSES - Trébuchon, JF (BOIS & FORETS DES TROPIQUES, 2022)
FAO, UNECE, 2021. FOREST SECTOR OUTLOOK STUDY 2020-2040. SWITZERLAND, UNITED NATIONS (UN), UNITED NATIONS ECONOMIC COMMISSION FOR EUROPE (UNECE), FOOD AND AGRICULTURE ORGANIZATION (FAO), 103 P. FAO, UNECE, 2021. FOREST PRODUCTS ANNUAL MARKET REVIEW 2020-2021. SWITZERLAND, UNITED NATIONS (UN), UNITED NATIONS ECONOMIC COMMISSION FOR EUROPE (UNECE), FOOD AND AGRICULTURE ORGANIZATION (FAO), 103 P. PAVAN KUMAR, RAM KUMAR SINGH, MANOJ KUMAR, MEENU RANI, PARDEEP SHARMA (EDS), 2021. CLIMATE IMPACTS ON SUSTAINABLE NATURAL RESOURCE MANAGEMENT. UNITED KINGDOM, WILEY BLACKWELL PUBLISHING, 384 P. BINKLEY D., 2021. FOREST ECOLOGY: AN EVIDENCE-BASED APPROACH. UNITED STATES, WILEY BLACKWELL PUBLISHING, 288 P. BIBIKHIN V., TAIT A. (TRANS.), 2021. THE WOODS. UNITED STATES, WILEY BLACKWELL PUBLISHING, 416 P. ASNAWI I., 2019. L’ESPRIT DE LA JUNGLE. FRANCE, PRESSES UNIVERSITAIRES DE FRANCE (PUF), 128 P. BLASER J., FRIZZO J., NORGROVE L., 2021. NOT ONLY TIMBER – THE POTENTIAL FOR MANAGING NON-TIMBER FOREST PRODUCTS IN TROPICAL PRODUCTION FORESTS – A COMPREHENSIVE LITERATURE REVIEW. INTERNATIONAL TROPICAL TIMBER ORGANIZATION (ITTO), PRECIOUS FORESTS FOUNDATION, 84 P. HELD C., MEIER-LANDSBERG E., ALONSO V., 2021. TROPICAL TIMBER 2050 – AN ANALYSIS OF THE FUTURE SUPPLY AND DEMAND FOR TROPICAL TIMBER AND ITS CONTRIBUTIONS TO A SUSTAINABLE ECONOMY. INTERNATIONAL TROPICAL TIMBER ORGANIZATION (ITTO), 78 P. QUENTIN GRAFTON R., LONG CHU H., NELSON H., BONNIS G., 2021. A GLOBAL ANALYSIS OF THE COST-EFFICIENCY OF FOREST CARBON SEQUESTRATION OECD ENVIRONMENT WORKING PAPERS 185, 67 P.